Evaluation Of Methane Dilution Capacity Of A Blowing Face Ventilation System Using A Water Sprayfan And Dust Scrubber - Charles D. Campbell; W. Allen Dupree (Society for Mining, Metallurgy & Exploration, 1991)
A field investigation was conducted by the Ventilation Division, Pittsburgh Health Technology Center (PHTC), Mine Safety and Health Administration (MSHA) to evaluate the effectiveness of a blowing face ventilation system utilizing a water sprayfan system and a single inlet flooded bed dust collector (scrubber) in controlling methane liberation in the face area while mining at brattice distances up to 12.2 meters (40 feet) from the face. The rated capacity of the scrubber was 117 m3/s (4,145 cfm) of air. Results from the investigation indicated a methane dilution capacity of 0.57 m3/s (20 cfm) with the air quantity behind the line brattice averaging 138.7 m3/s (4,900 cfm).